2009
DOI: 10.1111/j.1600-079x.2009.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects kidney grafts from ischemia/reperfusion injury through inhibition of NF‐kB and apoptosis after experimental kidney transplantation

Abstract: Free radicals are involved in pathophysiology of ischemia/reperfusion injury (IRI). Melatonin is a potent scavenger of reactive oxygen and nitrogen species. Thus, this study was designed to elucidate its effects in a model of rat kidney transplantation. Twenty Lewis rats were randomly divided into 2 groups (n = 10 animals each). Melatonin (50 mg/kg BW) dissolved in 5 mL milk was given to one group via gavage 2 hr before left donor nephrectomy. Controls were given the same volume of milk only. Kidney grafts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 43 publications
9
78
0
3
Order By: Relevance
“…MMP9 is activated by reactive oxygen species and its expression is likely to be regulated by oxidative stress (Rajagopalan et al 1996, Mori et al 2004, Pustovrh et al 2005. Studies in the literature indicate that melatonin significantly inhibits the translocation and binding of NF-kB to DNA in rat spleen and downregulates the expression of NF-kB/p65 in the pathophysiology of ischemia/reperfusion injury in a model of rat kidney transplantation (Chuang et al 1996, Li et al 2009). We observed that melatonin inhibited the nuclear translocation of p65 in IL1b-treated HUVECs and downregulated p65 and MMP9 proteins expression.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 is activated by reactive oxygen species and its expression is likely to be regulated by oxidative stress (Rajagopalan et al 1996, Mori et al 2004, Pustovrh et al 2005. Studies in the literature indicate that melatonin significantly inhibits the translocation and binding of NF-kB to DNA in rat spleen and downregulates the expression of NF-kB/p65 in the pathophysiology of ischemia/reperfusion injury in a model of rat kidney transplantation (Chuang et al 1996, Li et al 2009). We observed that melatonin inhibited the nuclear translocation of p65 in IL1b-treated HUVECs and downregulated p65 and MMP9 proteins expression.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin, a pineal secretory product, reduces the IRinduced brain, 12 heart, 13 kidney, 14,15 and liver 16 damages in rats. These effects of melatonin are related with scavenging of a variety of toxic oxygen and nitrogen-based reactants and stimulation of antioxidative enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit juice of Morinda citrifolia is a well-known health drink and has various pharmacological properties including antioxidant and anti-inflammatory effects (5,6,8,11,15). On the other side, very few studies have been made on antiischemic effect of Morinda citrifolia and those studies related to the effects on brain damage associated with IRI (7,9).…”
Section: Discussionmentioning
confidence: 99%